Application of indicator systems for monitoring and assessment of desertification from national to global scales - Sommer S; Zucca, Claudio; Grainger A; Cherlet, M.; Zougmoré, Robert B.; Sokona Y; Hill J; Della Peruta R; Roehrig J; Wang G (Wiley, 2011)
This paper suggests how the United Nations Convention to Combat Desertification (UNCCD) community can progressively make use of a flexible framework of analytical approaches that have been recently developed by scientific research. This allows a standardized but flexible use of indicator sets adapted to specific objectives or desertification issues relevant for implementing the Convention. Science has made progress in understanding major issues and proximate causes of dryland degradation such that indicator sets can be accordingly selected from the wealth of existing and documented indicator systems. The selection and combination should be guided according to transparent criteria given by existing indicator frameworks adapted to desertification conceptual frameworks such as the Dryland Development Paradigm and can act as a pragmatic entry point for selecting area- and theme-specific sets of indicators from existing databases. Working on different dryland sub-types through a meaningful stratification is proposed to delimit and characterize affected areas beyond the national level. Such stratification could be achieved by combining existing land use information with additional biophysical and socio-economic data sets, allowing indicator-based monitoring and assessment to be embedded in a framework of specific dryland degradation issues and their impacts on key ecosystem services.